Diet‐induced Alzheimer's‐like syndrome in the rabbit. Issue 1 (1st February 2022) - Weiss, Craig; Bertolino, Nicola; Procissi, Daniele; Aleppo, Grazia; Smith, Quinn C.; Viola, Kirsten L.; Bartley, Samuel C.; Klein, William L.; Disterhoft, John F.
Abstract: Introduction: Although mouse models of Alzheimer's disease (AD) have increased our understanding of the molecular basis of the disease, none of those models represent late‐onset Alzheimer's Disease which accounts for >90% of AD cases, and no therapeutics developed in the mouse (with the possible exceptions of aduhelm/aducanumab and gantenerumab) have succeeded in preventing or reversing the disease. This technology has allowed much progress in understanding the molecular basis of AD. To further enhance our understanding, we used wild‐type rabbit (with a nearly identical amino acid sequence for amyloid as in humans) to model LOAD by stressing risk factors including age, hypercholesterolemia, and elevated blood glucose levels (BGLs), upon an ε3‐like isoform of apolipoprotein. We report a combined behavioral, imaging, and metabolic study using rabbit as a non‐transgenic model to examine effects of AD‐related risk factors on cognition, intrinsic functional connectivity, and magnetic resonance‐based biomarkers of neuropathology. Methods: Aging rabbits were fed a diet enriched with either 2% cholesterol or 10% fat/30% fructose. Monthly tests of novel object recognition (NOR) and object location memory (OLM) were administered to track cognitive impairment. Trace eyeblink conditioning (EBC) was administered as a final test of cognitive impairment. Magnetic resonance imaging (MRI) was used to obtain resting state connectivity and quantitative parametric data (R2 *). Results: Experimental diets induced hypercholesterolemia or elevated BGL. Both experimental diets induced statistically significant impairment of OLM (but not NOR) and altered intrinsic functional connectivity. EBC was more impaired by fat/fructose diet than by cholesterol. Whole brain and regional R2 * MRI values were elevated in both experimental diet groups relative to rabbits on the control diet. Discussion: We propose that mechanisms underlying LOAD can be assessed by stressing risk factors for inducing AD and that dietary manipulations can be used to assess etiological differences in the pathologies and effectiveness of potential therapeutics against LOAD. In addition, non‐invasive MRI in awake, non‐anesthetized rabbits further increases the translational value of this non‐transgenic model to study AD.